The Power of Trendy Flash Intro Builder 1.0 in the Teaching of Grammar - Varia Virdania Virdaus; Saiful Rifa’i (Journal of Development Research, 2023)
The purpose of the study was to look into the effectiveness of Trendy Flash Builder 1.0 software in teaching grammar. This study used a non-random sample of students from all demographics and a non-randomized pretest-posttest control group design. The subject of the study was implemented in the English department of UNIPA Blitar. The research subject for this study was a student from two classes, IA and IB, from which the treatment class was drawn at random. Class IB was the experimental group, receiving Trendy Flash Builder 1.0 software as a teaching medium, whereas Class IA was the control group, receiving no teaching media. As these groups differed on several parameters, ANCOVA was employed to try to reduce some of these disparities. As a result of data calculations, the research hypothesis was confirmed. It is possible to infer that Trendy Flash Builder 1.0 software as a teaching medium can have a significant impact on students' grammar achievement.